The Effectiveness of Mindfulness-Based Cognitive Therapy Group in Decreasing Depression and Increasing Quality of Life in Women with Addicted Husbands - mahjoobeh alimoradi; soosan didehdar; hamid zolfaghari; vahid mostafapour; hossein farrokhi (Fasa University of Medical Sciences, 2019)
Background & Objective: Addiction as a disease is a disadvantage that affects the quality of life of families and couples and may cause depression among other members of the family. The purpose of this study was to investigate the effectiveness of Mindfulness-Based Cognitive Therapy Group in decreasing depression and increasing the quality of life in women with addicted husbands. Material & Methods: The semi-experimental design was pre-test-posttest with control group. The statistical population included all women with addicted husbands referring to the comprehensive health center of Fasa into the experimental and control groups (15 women in each group). The experimental group received 8 sessions of mindfulness-based cognitive-group therapy, and no intervention was provided to the control group members. The research instrument questionnaire was Beck and Quality of Life. Results: The results showed that mindfulness-based cognitive-group therapy was effective in depression and quality of life of women with addicted husbands (P<0.001) and treatment reduced depression and increased the quality of life of women in post-test of the experimental group. Conclusion: The results show that Mindfulness-Based Cognitive Therapy Group is effective in decreasing depression and, consequently, increasing the quality of life of addicted spouse.